Exploring Benchmarks for BOC Valuation and Trade Facilitation - Mendoza, Ronald U (Archīum Ateneo, 2015)
At the Philippine Bureau of Customs, given the present high risk of systematic undervaluation, improving the accuracy and precision of import valuation will most likely contribute to increased government revenues. More importantly, this can also help shore up importers’ support for present reforms in the BOC. In the Philippines, the reforms are also underpinned by a strategy to increase the openness of the BOC through its “Customs ng Bayan” website. Stakeholders can now download information on the valuation and assessed taxes on all products imported throughout the country’s 17 collection districts. A detailed analysis of import valuation patterns using this dataset can reveal whether and to what extent valuation patterns are beginning to reflect improved accuracy and precision. This, in turn, can be used as part of overall efforts to assess the relative improvements in trade facilitation. This note thus attempts to show how such an analysis can be done.